2018
DOI: 10.1080/14767058.2018.1474871
|View full text |Cite
|
Sign up to set email alerts
|

Role of ischemia-modified albumin in the evaluation of oxidative stress in intrahepatic cholestasis of pregnancy

Abstract: Serum IMA levels did not differ between pregnant women with ICP and healthy pregnant women, while the IMAR was significantly higher in the ICP group versus the healthy pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…In the presence of hypoxia and increased oxidative stress, the N-terminus of albumin changes, reducing its metal-binding ability, and a new form of albumin, IMA, is formed [9]. Studies have shown increased IMA levels in patients with preeclampsia, pregnancy cholestasis, and hyperemesis gravidarum [29][30][31]. In our study IMA level between groups was similar.…”
Section: Discussionsupporting
confidence: 60%
“…In the presence of hypoxia and increased oxidative stress, the N-terminus of albumin changes, reducing its metal-binding ability, and a new form of albumin, IMA, is formed [9]. Studies have shown increased IMA levels in patients with preeclampsia, pregnancy cholestasis, and hyperemesis gravidarum [29][30][31]. In our study IMA level between groups was similar.…”
Section: Discussionsupporting
confidence: 60%
“…The formation of reactive oxygen species (ROS) and free radicals temporarily changes the N-terminal region of albumin, which causes an increase in IMA concentration ( 7 ) . Furthermore, it has been shown to increase in the healthy pregnant women and other pregnancy-related situations ( 8 , 9 , 10 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Most scholars consider that the pathogenesis of this disease is notably correlated with maternal bile acid level, especially the CG level in the body of pregnant women (3). Long-term high bile acid level, especially high CG level will cause significant spasm in vessels on the surface of placental villi (4), and the increased resistance caused by it will lead to reduced blood flow passing through the area of placenta intervillous space and decreased oxygenation (4), and further bring about insufficient fetal perfusion (5), functional hypoxia-ischemia, difficulty in transshipment of oxygen molecules and nutrient substance from maternal circulation. This will finally result in intrauterine fetal distress and affect growth and development of fetuses (6).…”
Section: Introductionmentioning
confidence: 99%